2014
DOI: 10.22146/ijc.21257
|View full text |Cite
|
Sign up to set email alerts
|

Antiplasmodial Evaluation of One Compound from <i>Calophyllum flavoranulum</i>

Abstract: 0, 31,33, 40, 30.67, 46 dan 34% pada konsentrasi sampel berturut-turut 1,1x10 -10

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 15 publications
0
2
0
1
Order By: Relevance
“…Berdasarkan penelitian yang dilakukan oleh Prasiwi dan kawan-kawan, didapatkan dosis efektif untuk mengobati penyakit malaria pada mencit yaitu sebesar 0,084 g/KgBB dimana didapatkan data persentase penghambatan pertumbuhan Plasmodium berghei sebesar 54,06%. 12 Penelitian lainnya yang telah dilakukan mengenai ekstrak dari tumbuhan herbal seperti ekstrak tumbuhan berbunga Asteraceae dan Rubiaceae families 13 , daun bunga nusa indah (Mussaenda erythrophylla) 13 , daun nyamplung (Calophyllum flavoranulum) 14 , daun kedondong hutan (Spondias pinnata) 15 , dan kulit batang gambilo (Gardenia ternifolia) 16 . doi:10.24843.MU.2023.V12.i8.P03 dengan kandungan bahan aktif seperti alkaloid, terpen, antrakuinon, flavonoid, tannin, saponin, dan steroid.…”
Section: Pembahasanunclassified
“…Berdasarkan penelitian yang dilakukan oleh Prasiwi dan kawan-kawan, didapatkan dosis efektif untuk mengobati penyakit malaria pada mencit yaitu sebesar 0,084 g/KgBB dimana didapatkan data persentase penghambatan pertumbuhan Plasmodium berghei sebesar 54,06%. 12 Penelitian lainnya yang telah dilakukan mengenai ekstrak dari tumbuhan herbal seperti ekstrak tumbuhan berbunga Asteraceae dan Rubiaceae families 13 , daun bunga nusa indah (Mussaenda erythrophylla) 13 , daun nyamplung (Calophyllum flavoranulum) 14 , daun kedondong hutan (Spondias pinnata) 15 , dan kulit batang gambilo (Gardenia ternifolia) 16 . doi:10.24843.MU.2023.V12.i8.P03 dengan kandungan bahan aktif seperti alkaloid, terpen, antrakuinon, flavonoid, tannin, saponin, dan steroid.…”
Section: Pembahasanunclassified
“…Abbas and Syafruddin (2010) successfully isolated the compound of xanthon that is fenil kaumarin from Calophyllum flavoranulum from Kalimantan and reported its antiplasmodial activity invivo in mencit that was infected by Plasmodium Berghei. 19 Rissyelly (2010) also reported antiplasmodial activity of ksanton compound namely [2-(3',3'-dimetilalil)-1,3,7-trihidroksiksanton] from Calophyllum canum. 20 The changes in morphology and ultra structure of P. falciparum 3D7 after being exposed to hexane fraction extract C. bicolor might be related to the mechanism and target of given anti plasmodial.…”
Section: Figure 2 Vacuole Membrane Boundary and Hemozoinmentioning
confidence: 99%
“…The scientific study of the genus Calophyllum revealed that it is a rich source of bioactive secondary metabolites showing a wide range of biological activities. Some coumarins from C. flavoranulum showed activity against Plasmodium berghei parasite [ 13 ].…”
Section: Introductionmentioning
confidence: 99%